Qualidade na distribuição física do e-commerce: um estudo sobre as práticas de qualidade em uma rede de transportadores regionais terceirizados do segmento de e-commerce - Castex, Luís Augusto (2018)
The purpose of this study is to define a methodology to identify the most effective quality management practices in an e-commerce carrier’s third party last mile transportation network. The defined methodology will be applied in the search for best practices that might be used in a supplier development program. A survey, based on quality management literature review, was elaborated and tested with the transportation network companies. This test was also followed by some interviews. Through these interviews it was not only possible to identify different and effective practices among best performance transportation companies, but also confirm the factors that seem to positively affect service quality, like leadership commitment with quality management. Therefore, the developed methodology revealed to be effective to develop an excellence program for an e-commerce carrier’s network of deliveries suppliers and thus enhance its competitiveness.